ANALYSIS OF FLOOD HYDROGRAPH IN THE LANDAK SUB WATERSHED - Miranda, Juwita; Soeryamassoeka, SB; Gunarto, Danang (Jurnal Teknik Sipil, 2023)
This research is motivated by the natural flooding disaster in the Landak sub-watershed area, which can be caused by river overflow due to high rain intensity. Flood discharge can be calculated using the Synthetic Unit Hydrograph method if the available data is limited, such as only obtaining rainfall data and watershed characteristics.Several Synthetic Unit Hydrograph (SUH) methodologies, including SUH Snyder, Nakayasu, Soil Conservation Services (SCS), Gama I, ITB, and Limantara, were utilized in this study. The analyzed data included precipitation data and measured discharge data. Rainfall data are analyzed using the homogeneity test, statistical descriptors, and chi-squared to determine the planned flood discharge. Then, continue with the study of rainfall frequency and analysis of rainfall intensity so that the maximal discharge can be analyzed using three SUH methods: HSS Snyder, Nakayasu, and SCS. The analysis of measured release is conducted by statistically analyzing estimated discharge data.The analysis results are then compared to obtain the percentage error between the discharge plan and the minimum measured discharge. The results showed that the HSS Snyder method was selected for analyzing flood discharge in the Landak sub-watershed basin because it has the minimum percentage error from comparing planned release and measured discharge values. Therefore, for the calculation of flood discharge analysis of the Landak sub-watershed basin, the HSS Snyder method is used with the acquisition of flood discharge plans for the return period of 2, 5, 10, 20, 50, and 100 years of 648,880 m3/sec, 896,335 m3/sec, 1025,954 m3/sec, 1132,006 m3/sec, 1252,788 m3/sec, 1335,273 m3/sec.